Internal Quality Audit Administration Information System In Badan Penjaminan Mutu (Case Study: Universitas Lancang Kuning) - Bayu Febriadi (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2019)
Lancang Kuning University Mapping and Implementation of the Internal Quality Assurance System (SPMI) was implemented from 2008 with the establishment of the Quality Assurance Agency (BPM) and Quality Assurance Unit (UPM) at the Faculty level with the aim of creating a quality culture in the Lancang Kuning University Academic Community, in the process of implementing the internal quality assurance system at the quality assurance agency, it has also carried out Monitoring and Evaluation (Monev) once a year to guarantee the quality culture that has been implemented, but in the implementation of Monitoring and Evaluation the Quality Assurance Agency always experiences obstacles such as technical, technical and recording data during activities and also in document archiving because there is no media that can be utilized in managing monitoring and evaluation while the application of information technology and resources already exists. With the use of information technology in the application of computerized based applications for filing and presenting data needs, it is expected to help the academics more quickly and precisely in processing data monitoring and evaluation as well as a means of implementing accreditation by the National Accreditation Board of Higher Education (BAN-PT). It is expected that with the development of applications in the management of monitoring and evaluation by completing the System Development Lyfe Cycle (SDLC) method in the problem analysis phase, the application that is built can improve the quality of monitoring and evaluation in data processing that is well integrated and can be utilized at any time by Lancang Kuning University academic community.